Factor Substitution and Endogenous Growth - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2001)
We argue that the degree of substitutability between skilled and unskilled workers in production increases long-term income growth rate. Growth rate reaches its maximum when such factors are perfect substitutes, but falls to zero when they are perfect complements. This model brings together the diverging relative wage and the human-capital-growth literature. Easier substitution absorbs more workers into the skilled profession, and their training fuels human capital accumulation and growth. Our result implies, among other things, that growth is positively related to between-and within-group inequality.